Serum Inflammatory Biomarkers Contribute to the Prognosis Prediction in High-Grade Glioma - Chen, Xiao-Yong; Pan, Ding-Long; Xu, Jia-Heng; Chen, Yue; Xu, Wei-Feng; Chen, Jin-Yuan; Wu, Zan-Yi; Lin, Yuan-Xiang; You, Hong-Hai; Ding, Chen-Yu; Kang, De-Zhi (Frontiers in Oncology, 2022)
Background: To evaluate the prognostic value of serum inflammatory biomarkers and develop a risk stratification model for high-grade glioma (HGG) patients based on clinical, laboratory, radiological and pathological factors. Materials and Methods: A retrospective study of 199 patients with HGG was conducted. Patients were divided into a training cohort (n=120) and a validation cohort (n=79). The effects of potential associated factors on the overall survival (OS) time were investigated and the benefits of serum inflammatory biomarkers in improving predictive performance was assessed. Univariable and multivariable Cox regression analyses, the least absolute shrinkage and selection operator (LASSO) regression analysis, and support vector machines (SVM) was used to select variables for the final nomogram model. Results: After multivariable Cox, LASSO, and SVM analysis, in addition to other 3 clinic-pathologic factors, platelet-to-lymphocyte ratio PLR > 144.4 (hazard ratio HR, 2.05; 95 confidence interval CI, 1.25-3.38; P = 0.005) were left for constructing the predictive model. The model with PLR exhibited a better predictive performance than that without them in both cohorts. The nomogram based on the model showed an excellent ability of discrimination in the entire cohort (C-index, 0.747; 95% CI, 0.706-0.788). The calibration curves showed good consistency between the predicted and observed survival probability. Conclusion: Our study confirmed the prognostic value of serum inflammatory biomarkers including PLR and established a comprehensive scoring system for the OS prediction in HGG patients.